2020
DOI: 10.1364/ol.45.000686
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth plasmonics for extraordinary light absorption in deep sub-wavelength geometries

Abstract: In this Letter, we demonstrate an ultra-broadband metamaterial absorber of unrivaled bandwidth (BW) using extraordinary optical response of bismuth (Bi), which is the material selected through our novel analysis. Based on our theoretical model, we investigate the maximum metalinsulator-metal (MIM) cavity BW, achievable by any metal with known n-k data. We show that an ideal metal in such structures should have a positive real permittivity part in the near-infrared (NIR) regime. Contrary to noble and lossy meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In recent years, many absorbers with different structures have been proposed for visible-infrared spectroscopy. One of the most common is single-band or multi-band absorption through metal-insulatormetal (MIM) structures [10][11][12]. Due to its resonant characteristics, this structure can achieve high absorption, but it has a narrow absorption bandwidth within a certain band range [13].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many absorbers with different structures have been proposed for visible-infrared spectroscopy. One of the most common is single-band or multi-band absorption through metal-insulatormetal (MIM) structures [10][11][12]. Due to its resonant characteristics, this structure can achieve high absorption, but it has a narrow absorption bandwidth within a certain band range [13].…”
Section: Introductionmentioning
confidence: 99%
“…Biao Wu et al presented an ultra-broadband metamaterial absorber, with an absorptivity is greater than 90% in the 939–3988 nm waveband [ 39 ]. Imre Ozbay et al demonstrated an ultra-broadband metamaterial absorber with absorption above 0.9 in the waveband of 800–2390 nm by using the extraordinary optical response of bismuth (Bi) [ 40 ]. Although mid-infrared MAs have good performance, combining high absorptivity and broad bandwidth is still challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them are based on a Metal–Dielectric–Metal configuration, having specific absorption bandwidths, restricting their high performance applications 5 7 . Recent studies demonstrated an extraordinary absorption response from the Bi-based MPA in ultra-broadband, polarization insensitive, and almost omnidirectional NIR (near infrared) perfect absorber by using Bi nanodiscs in an metal–isolator–metal configuration 8 . The GST chalcogenide phase change materials, (this includes GeTe), can be quickly 9 and repeatedly 10 switched between amorphous and crystalline states by appropriate thermal, electric, or optical stimuli 11 13 .…”
Section: Introductionmentioning
confidence: 99%